First Instance of Using a Camera Trap to Study The Breeding Biology and Ecology of the Short-Toed Eagle in Altyn-Emel National Park in 2023 - Didar K. Bazarbekov; Altai Zh. Zhatkanbaev; Margulan T. Musabekov (Пернатые хищники и их охрана)
A Short-Toed Eagle (STE, Circaetus gallicus) nest was observed over the reproductive period of 2023, in Altyn-Emel National Park, located in the south-east of Kazakhstan (Zhetysus oblast of the Republic of Kazakhstan). The nest location was on the right bank of the Ile River in arid terrain of clay conglomerate, 12–15 km east of the dry lowland massif of Ulken Kalkan (Ile Forestry section “Zhagalybai”) near the “Kosbastau” area. The nest was built on a live Turanga poplar (Populus diversifolia) about 5 m high on one of two dried branching trunks in the apex of the tree at a height of 3.7 meters. Judging from the massiveness of the nesting structure, this was not the first year that this pair of snake eagles nested here. A nest of Saxaul Sparrow (Passer ammodendri) was located 50 m away on another turanga tree in a hollow formed by the fall of a dry branch (fully-feathered chicks observed May 8). At least one pair of Indian Sparrows (Passer indicus) was nesting in the mass of the STE nest.